Biomass-derived high-performance tungsten-based electrocatalysts on graphene for hydrogen evolution1. Issue 36 (28th September 2015) - Meng, Fanke; Hu, Enyuan; Zhang, Lihua; Sasaki, Kotaro; Muckerman, James T.; Fujita, Etsuko
<x xml:space="preserve">Abstract</x> Biomass-derived WSoy0.7GnP1.0, a composite of WC, W2C and WN on graphene, is a highly active and stable HER catalyst.